(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Wood is a product of woody plants, formed by a complex of tissues - conductive, mechanical, reserve and secretory. However, it is not just a mechanical mixture of chemical compounds, but a complex biological and physico-chemical system composed of polymers, monomers, made up of cell walls and cell cavities (lumens). The knowledge of its structure allows the tree species to be determined, the conditions under which it is formed, as well as its behavior under different loads. The paper examines the variation of the quantitative indicators of individual tissues and the possibility of using it to classify individual species.